Pengembangan perangkat pembelajaran matematika dengan pendekatan CTL materi segi empat kelas VII MTs Negeri 3 Siak - Azni Maziyatul Ilmiyah; Aulia Sthephani; Rezi Ariawan; Agus Dahlia; Riska Novia Sari (Journal of Didactic Mathematics, 2021)
The purpose of this research to describe the level validity of mathematics lesson plan by using the Contextual Teaching and Learning (CTL) Approach on Quadrangle Substance at Grade VII MTs Negeri 3 Siak which was valid test. The development model in this research used an R&D model with six stages were the researcher have modified depends on the needs and conditions with current situation now it’s covid-19 pandemic. These six stages arepotential and problems, data collection, product design, design validation, design revision and final product. The data collection technique used in this research was the validation of lesson plan, the kind of data collection instrument was the form of a validation sheet. While the data analysis technique used in the form of descriptive analysis by describing the validity of the lesson plan which was developed by the researcher. The results of this research, the RPP validation were 85.86% with very valid criteria. While the results of LKPD validation were 89.81% with very valid criteria. Based on the results of this research, it can be concluded that the development of mathematics lesson plan with a Contextual Teaching and Learning (CTL) approach on quadrangle substance at grade VII MTs Negeri 3 Siak has been suitable for the validity.